A Note on the Amphibian Fauna at Pantai Melawi Bachok, Kelantan - Belabut, Daicus; Hashim, Rosli; Yong, Hoi Sen; Mat Diah, Siti Zaleha; Ahmad, Norhayati; Lim, Boo Liat (Malaysian Journal of Science, 2010)
Five species of amphibians were found at Melawi, Bachok, Kelantan. Kaloula pulchra, Fejervarya limnocharis and Duttaphrynus melanostictus were the predominant species. Only a single individual of Polypedates leucomystax and an exotic species Hoplobatrachus rugulosus respectively was also found here. ABSTRAK Lima spesies amfibia dijumpai di Melawi Bachok, Kelantan. Kaloula pulchra, Fejervarya limnocharis dan Duttaphrynus melanostictus adalah spesies yang paling kerap ditemui dan masing-masing satu individu Polypedates leucomystax dan spesies eksotik Hoplobatrachus rugulosus dijumpai di kawasan ini. (Keywords: anurans, sandy habitat, bioindicator, Kelantan.)